2022
DOI: 10.1007/s00296-021-05083-z
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of juvenile idiopathic arthritis and type 1 diabetes: a case-based review

Abstract: The study was aimed to review a rare coexistence of type 1 diabetes (T1D) and juvenile idiopathic arthritis (JIA) regarding different clinical approaches to the management and treatment options. Medical complications of the two autoimmune disorders in children and adolescents have been evaluated, particularly in those treated with glucocorticosteroids (GCS) and insulin. A review of the literature regarding reports on concomitant T1D and JIA was conducted using resources available in Medline, Google Scholar, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…For instance, a case-control study demonstrated that each IQR increase in PFOA exposure was associated with a 69% increase in the risk of RA [ 30 ]. Moreover, individuals with arthritis are more susceptible to diabetes and other metabolic diseases [ 11 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a case-control study demonstrated that each IQR increase in PFOA exposure was associated with a 69% increase in the risk of RA [ 30 ]. Moreover, individuals with arthritis are more susceptible to diabetes and other metabolic diseases [ 11 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations of genes that cause T-cell dysfunction (e.g., HLA, CTLA4, and PTPN22) may be involved in the development of these conditions [91]. On the other hand, diabetes may be facilitated by the adverse effects of frequent corticosteroid use on JIA flairs [92].…”
Section: T1d and Other Aidsmentioning
confidence: 99%
“…Hence, the immune-modulatory effect may have a role in preventing the immune cascade responsible for the onset of T1D, suggesting that an earlier start of these effective drugs may have a protective effect on beta cell preservation. Moreover, the use of disease-modifying antirheumatic drugs has been associated with a significant improvement in HbA1c and a reduced need for insulin [92], hence these therapies in JIA may impact the risk of developing T1D and/or improve T1D disease course [95][96][97][98][99].…”
Section: T1d and Other Aidsmentioning
confidence: 99%
“…There are variability in the prevalence of adolescent T1DM with the highest incidence of T1DM reported in the United States (US), India and Brazil 4 . There is a huge economic burden from the chronic nature of the disease due to its multiple short and long-term complications, presenting it as a global health crisis to handle 5 .…”
Section: Introductionmentioning
confidence: 99%